Criminal procedure : theory and practice - Ingram, Jefferson (New York, NY : Routledge, 2022)
"Criminal Procedure: Theory and Practice, 3rd Edition, presents a broad overview of criminal procedure as well as a detailed analysis of specific areas of the law that require specialized consideration. The third edition provides students with an updated, comprehensive text written in reader-friendly language to introduce them the field of criminal procedure. Significant edited legal cases are integrated into each chapter, and comments, notes and questions accompany each case. This edition features a new chapter covering searches of Internet-connected devices and electronic devices that may store personally-connected data. The chapter, The Internet of Things, introduces search and seizure concepts related to electronics. In addition, a section at the conclusion of each chapter, How Would You Decide, allows readers to examine the facts of a real case that contain some of the important concepts form each chapter. The reader can compare his/her resolution of the case with the way the actual court determined the issue. Using a balanced text/case format, the author provides an overview of general criminal procedure as well as guidance for law enforcement actions that honor constitutional protections and comport with the rule of law. Instructor support material prepared by the author is available on our website, including lecture slides and instructor's manual with test bank, as well as online updates on new case law in the area of criminal procedure. This textbook is ideal for all Criminal Justice programs, in both 4-year and 2-year schools, especially those preparing future police officers, as well as a reference for law students, and attorneys"--
Introduction to the Constitutional and Legal Process -- Basic Fourth Amendment Principles and the Exclusionary Rule -- Stop and Frisk and Constitutional Concepts -- Arrest and Related Concepts -- Miranda Warnings and Requirements -- Obtaining and Using Search Warrants : Practice, Execution, and Return -- Searches and Seizures : Places, Persons and Vehicles -- The Internet of Things : Searches of Computers, Cell Phones, and Other Smart DevicesChapter -- Searches of Open Fields and Abandoned Property -- Special Needs Searches -- Confessions and the Fifth Amendment -- Pretrial Criminal Process : Pretrial Motions, Identification Process, Preliminary Hearing, Bail, Right to Counsel, Speedy Trial, and Double Jeopardy -- Trial Procedure and Legal Rights -- Appellate Practice and Other Post-trial Remedies.
OCLC-licensed vendor bibliographic record.
Keywords: Criminal procedure -- United States; LAW / Criminal Law / General; LAW / Criminal Procedure; SOCIAL SCIENCE / Criminology